Bacterial isolation and antimicrobial susceptibilities in patients with infective endocarditis - Somporn Srifuengfung (2018)
Infective endocarditis is life-threatening and urgent treatment is needed. We review here 6,217 patients with infective endocarditis admitted to Siriraj Hospital during a 20 year period, 1982-2001. In this retrospective study, we obtained our data from hemoculture results. Bacterial pathogens were found in only 834 patients (13.41%). Of the five most common pathogens, nonfermentative gram-negative rods (N.F.) ranked first (20.94%), followed by coagulase-negative staphylococci (12.47%), viridans streptococci (10.23%), Staphylococcus aureus (9.29%), and Escherichia coli (8.59%). Of the N.F., the sensitivities were: cefoperazone/sulbactam (86%), piperacillin/tazobactam (86%), meropenem (84%), imipenem (83%), ceftazidime (78%), ofloxacin (85%), ciprofloxacin (71%), and co-trimoxazole (71%).